Modeling, Analysis, Evaluation And Experimental Investigation Of Abrasive Blasting Process - Singh, Gurdeep (My University, 2013)
Abrasive blasting is the operation widely used to smooth a rough surface, roughen a smooth surface, shape a surface, or remove surface contaminants. The effect of shot blasting treatment using steel shot balls on the surface characteristics of four different metals has been studied in this thesis work. Mainly focusing on output response parameters like Percentage weight loss, surface roughness, micro hardness and surface characteristics, a comparison study of Abrasive blasting using different blasting times is made. Graph theory is applied to the Abrasive blasting system for structural modeling, characterization and integrative analysis of Abrasive blasting system. System permanent function is developed which can be used to find numerical index of an Abrasive blasting system by substituting the numerical values of subsystems and their interactions.
ME, MED
Keywords: ABS; Abrasive Blasting; Steel Shots; Graph Theory; Permanent Function